Disciplining Urbanites in Contemporary Guayaquil - Andrade, Xavier (2007)
This ethnographic piece discusses the construction of “regenerated subjects”, a form of political subjectivity that forms a part of the process of urban renovation implanted by the local administration of Guayaquil for something more of one period. The object of study is a course of the municipal program of learning (“Aprendamos: una oportunidad para superarnos”) destined to foment concepts of “citizenship for everyone”.